Complete chloroplast genome of Oryza sativa L. (B810s) and its phylogenetic analysis (Bangladesh Journal of Botany, 2021)
The complete chloroplast (cp) genome of Oryza sativa L.(B810S) was 134546 bp in length in the study, which contains 149 genes including 99 coding protein genes, 41 transfer RNA genes, 8 ribosomal RNA genes and 1 non-coding region by gene annotation. A total of 20879 amino acids were encoded by this cp genome, TTT (Phe) and TTG (Leu) codon were the most frequent amino acids, whereas the ACC (Thr), GCC (Ala), CTC (Leu), and AAC (Asn) codon were the least frequent ones. The content of the four bases on the cp genome were 30.6% for A, 30.4% for T, 19.4% for C and 19.6% for G, respectively. Obviously, the A+T (61.0%) content is more higher than G+C (39.0%). The gene order and content are the same as those of previously reported cp genome of Rice. Phylogenetic analysis was implemented based on concatenated amino acid sequences of 99 protein-coding genes using Neighbor-Joining method (NJ) method. Therefore, the complete B810S cp genome provides interesting insights and valuable information that can be used to identify related species and reconstruct its phylogeny.Bangladesh J. Bot. 50(3): 895-901, 2021 (September) Special